2014
DOI: 10.11622/smedj.2014091
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum visfatin as a risk factor for atherosclerosis in patients with ischaemic cerebrovascular disease

Abstract: RESULTSThe mean serum visfatin level of the patients in Group B was higher than that in Group A (75.5 ± 77.80 ng/mL vs.8.6 ± 4.69 ng/mL; p < 0.05) and the level was higher in patients from Group B2 than those from Group B1 (89.0 ± 80.68 ng/mL vs. 50.4 ± 72.44 ng/mL; p < 0.05). Multivariate regression analysis showed that CCA-IMT values were not significantly associated with visfatin levels. However, logistic regression analysis showed that serum visfatin was an independent risk factor for atherosclerosis (odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…NAMPT is elevated in symptomatic atherosclerotic carotid plaque [13], and increased serum levels of NAMPT have been associated with recent ischemic cerebral events in patients with carotid atherosclerosis [27]. Our findings in the present study suggest that increased NAMPT expression in atherosclerotic disorders is not restricted to immune cells within the atherosclerotic lesion, but is also found in circulating mononuclear cells.…”
Section: Discussionsupporting
confidence: 58%
“…NAMPT is elevated in symptomatic atherosclerotic carotid plaque [13], and increased serum levels of NAMPT have been associated with recent ischemic cerebral events in patients with carotid atherosclerosis [27]. Our findings in the present study suggest that increased NAMPT expression in atherosclerotic disorders is not restricted to immune cells within the atherosclerotic lesion, but is also found in circulating mononuclear cells.…”
Section: Discussionsupporting
confidence: 58%
“…ischemic cerebrovascular events associated with carotid atherosclerosi. 13) In this study, we found that NAMPT is expressed not only in atherosclerotic plaques, but also it increased in the PBMC and the plasma in the patients with ACS compared with the normal subjects. Moreover, the expression of extracellular NAMPT (eNAMPT) was related to the M2 polarization of peripheral blood macrophages in patients with ACS; eNAMPT is associated with immunosuppressive M2 macrophages.…”
Section: Discussionmentioning
confidence: 53%
“…Increased visfatin promotes the proliferation of vascular smooth muscle cells and of fibroblasts, and plays a part in myocardial fibrosis and cardiac remodeling, which is an important process of hypertension [43]. Kong et al proved that increased serum visfatin levels were associated with the occurrence of atherosclerosis in patients with ischemic cerebral infarction [44]. These funding might suggest a potential role of this adipokine in vascular function.…”
Section: Discussionmentioning
confidence: 99%